Logistics Distribution Route Optimization Based on Improved Particle Swarm Optimization (Informatica, 2023)
This article improves the logistics distribution route and improves the distribution as well as transportation efficiency. The article combines the features of logistics dissemination along with mathematical designing of dissemination automobile routing issue. The mountain climbing procedure with strong local search ability is introduced into the particle swarm optimization (PSO) procedure to improve the offered approach. Two mountain climbing schemes are offered in this article, and two different hybrid (PSO) procedures are constructed. The experimental outcomes reveals the performance of Hybrid PSO scheme 1 and hybrid PSO scheme 2 offered in this paper which are better than that of standard PSO. Hybrid PSO scheme 2 offers best potential in efficiently solving the routing issue of logistics dissemination automobile. After the issue scale grows, the optimization advantages of Hybrid PSO scheme 2 are fully displayed. It was observed from the experimental analysis that using hybrid PSO scheme 2 to solve the logistics dissemination automobile routing issue can greatly shorten the dissemination mileage.